2012
DOI: 10.1063/1.3674322
|View full text |Cite
|
Sign up to set email alerts
|

Robust unipolar resistive switching of Co nano-dots embedded ZrO2 thin film memories and their switching mechanism

Abstract: The preparation and electrical properties of Ti/Co Embedded (Co-E) ZrO2/Pt resistive switching memories are investigated. The Co nano-dots are formed in ZrO2 thin film after the memory device is annealed at 600 °C in N2 ambient for 60 s without any chemical reaction between Co and ZrO2, which is confirmed from the transmission electron microscopy, energy dispersive X-ray analyzer, and X-ray photoelectron spectroscopy observations. The devices exhibit low forming voltage of −1.5∼−2.8 V and robust negative bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…16 Typical I-V characteristics of the stable switching cycles of the Cu/a-SiC/Au devices with 1 lm 2 device area are also shown in Figures 2(c) and 2(d), presenting all four unipolar switching modes, respectively. It is observed that typical V SET and V RESET are around or below 2 V. It is worth noting that, high switching ratios in the range of 10 6 -10 8 were obtained for all four modes. Asymmetric switching performances between positive bipolar and negative bipolar cycles as well as between positive unipolar and negative unipolar cycles are observed.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…16 Typical I-V characteristics of the stable switching cycles of the Cu/a-SiC/Au devices with 1 lm 2 device area are also shown in Figures 2(c) and 2(d), presenting all four unipolar switching modes, respectively. It is observed that typical V SET and V RESET are around or below 2 V. It is worth noting that, high switching ratios in the range of 10 6 -10 8 were obtained for all four modes. Asymmetric switching performances between positive bipolar and negative bipolar cycles as well as between positive unipolar and negative unipolar cycles are observed.…”
mentioning
confidence: 84%
“…All four possible modes of nonpolar resistive switching were achieved with ON/OFF ratio in the range 10 6 -10 8 . Detailed current-voltage I-V characteristics analysis suggests that the conduction mechanism in low resistance state is due to the formation of metallic filaments.…”
mentioning
confidence: 99%
See 3 more Smart Citations